A utilização da técnica moderna de Lester Horton como potencializador no corpo do dançarino cover de K-pop e a importância desse conhecimento para um(a) professor (a) de dança - SANTOS, Lauane Gabriele Gomes dos (2024)
This “Course Conclusion Paper - TCC”, entitled: “The Use of Lester Horton’s Modern Technique as a Enhancer in the Body of the K-Pop Cover Dancer and the importance of this knowledge for a dance teacher”. The research problem was: “How does Lester Horton’s technique contribute to preparing the body and improving the execution of the Kpop dancer’s movements?” related to the dance teacher training process and its contributions to K-Pop dancers and future dance teachers. For the development of its research methodology, the main theoretical contribution was the concept of “phenomenology” and the conception of correlational research, in order to base an understanding on the comparison of improvements in K-Pop dance movements based on the use of the technique by Lester Horton. The work was organized into three chapters: Chapter 1: TO UNDERSTAND K-POP BETTER; Chapter 2: DISCOVERIES AND EXPERIENCES WITH K-POP; Chapter 3: EXPERIENCE ON THE COURSE AND TEACHER TRAINING IN DANCE. The study aims to bring contributions to the community of K-Pop dancers, as well as to the academy since studies on the subject are still uncommon, and especially works that relate the subject of K-pop with the Lester Horton Technique.